Comparison of diagnostic accuracy of early screening for pre‐eclampsia by NICE guidelines and a method combining maternal factors and biomarkers: results of SPREE. (14th March 2018) - Tan, M. Y.; Wright, D.; Syngelaki, A.; Akolekar, R.; Cicero, S.; Janga, D.; Singh, M.; Greco, E.; Wright, A.; Maclagan, K.; Poon, L. C.; Nicolaides, K. H.
ABSTRACT: Objective: To test the hypothesis that the performance of first‐trimester screening for pre‐eclampsia (PE) by a method that uses Bayes' theorem to combine maternal factors with biomarkers is superior to that defined by current National Institute for Health and Care Excellence (NICE) guidelines. Methods: This was a prospective multicenter study (screening program for pre‐eclampsia (SPREE)) in seven National Health Service maternity hospitals in England, of women recruited between April and December 2016. Singleton pregnancies at 11–13 weeks' gestation had recording of maternal characteristics and medical history and measurements of mean arterial pressure (MAP), uterine artery pulsatility index (UtA‐PI), serum placental growth factor (PlGF) and serum pregnancy‐associated plasma protein‐A (PAPP‐A). The performance of screening for PE by the Bayes' theorem‐based method was compared with that of the NICE method. Primary comparison was detection rate (DR) using NICE method vs mini‐combined test (maternal factors, MAP and PAPP‐A) in the prediction of PE at any gestational age (all‐PE) for the same screen‐positive rate determined by the NICE method. Key secondary comparisons were DR of screening recommended by the NICE guidelines vs three Bayes' theorem‐based methods (maternal factors, MAP and PAPP‐A; maternal factors, MAP and PlGF; and maternal factors, MAP, UtA‐PI and PlGF) in the prediction of preterm PE, defined as that requiring delivery < 37 weeks. Results: All‐PE developed in 473 (2.8%) of the 16 747 pregnancies and preterm PE developed in 142 (0.8%). The screen‐positive rate by the NICE method was 10.3% and the DR for all‐PE was 30.4% and for preterm PE it was 40.8%. Compliance with the NICE recommendation that women at high risk for PE should be treated with aspirin from the first trimester to the end of pregnancy was only 23%. The DR of the mini‐combined test for all‐PE was 42.5%, which was superior to that of the NICE method by 12.1% (95% CI, 7.9–16.2%). In screening for preterm PE by a combination of maternal factors, MAP and PlGF, the DR was 69.0%, which was superior to that of the NICE method by 28.2% (95% CI, 19.4–37.0%) and with the addition of UtA‐PI the DR was 82.4%, which was higher than that of the NICE method by 41.6% (95% CI, 33.2–49.9%). Conclusions: The performance of screening for PE as currently recommended by NICE guidelines is poor and compliance with these guidelines is low. The performance of screening is substantially improved by a method combining maternal factors with biomarkers. © 2018 Crown copyright. Ultrasound in Obstetrics & Gynecology © 2018 ISUOG.